To determine the effect of parenteral iron in the management of symptoms related to restless leg syndrome in patients with iron deficiency anemia - Khan, Bughdad; Qureshi, Bilal Zeb; Naim, Fahad; Utmani, Nizamuddin; Khawaja, Tariq Mahfooz; Shah, Syed Hasnain Ali (International Journal of Pathology, 2025)
Background: The current study aimed to determine the frequency of restless leg syndrome (RLS) in patients with iron deficiency anemia (IDA) presenting to Khyber Teaching Hospital (KTH) and Khushal Medical Center (KMC) Peshawar and to see the effect of parenteral iron therapy on RLS with IDA. Methods: This prospective cohort study enrolled 110 patients of either gender with IDA from September 2022 to December 2023. All patients were interviewed and data was recorded for restless leg syndrome as per operational definition. The diagnosed RLS patients were given 500mg iron carboxymaltose in 100ml normal saline (NS) over a period of 15 minutes stats and 500mg after two weeks and treatment response was assessed four weeks after the treatment. Clinical symptoms including pain, fatigue and sleep quality were recorded before and after the iron therapy. All the data were analyzed using SPSS version 22.0. Results: RLS was observed in 35.5% patients with IDA. The mean age was 48.70±8.0 years. Male gender was 54.5% while female gender was 45.5% in our study. The levels of hemoglobin (Hb) were significantly improved with iron carboxymaltose (p-value <0.001). The symptoms related to RLS including pain, fatigue and quality of sleep were 90.1% improved after iron therapy. T-test reveals significant improvement in pain, fatigue and sleep quality before and after iron therapy with p-value <0.001. There was no statistical significant association between gender and improvement of symptoms related to RLS (p-value >0.05). Conclusion: RLS was highly prevalent in patients with IDA in our population. Management of IDA with parenteral iron carboxymaltose not only improves the levels of Hb but provide immediate relief of symptoms related to RLS.